Association of serum uric acid-creatinine ratio with microalbuminuria and glycemic status (HbA1c) as an early indicator of diabetic nephropathy - Kulkarni, Swathi; Yadav, Anurag (International Journal of Research in Medical Sciences, 2020)
Background: The serum uric acid is a good predictor of renal injury in both diabetes patients and non-diabetes. Creatinine is the marker to detect the renal function. Aim of our study was to assess the correlation of the serum uric acid to creatinine ratio with the Microalbuminuria and glycemic status (HbA1c) in diabetes mellitus patients. Methods: It is analytical observational study conducted in urban tertiary care hospital attached to medical college between July to august 2019 after obtaining the ethics clearance. Participants aged between 18 to 60 years with type 2 diabetes mellitus and healthy controls were included in present study. The patients with diabetic nephropathy with grade 3 and above and non-diabetes patients with history of ischemic heart disease, advanced hypertension, Chronic or acute kidney disease, liver disease, known case of hyperuricemia/gout, alcoholics, acute febrile illness, urinary tract infection, cancer were excluded from present study. Results: Total of 131 individuals were included in present study that fulfilled inclusion criteria. The mean age of the participants was 56.70±11.9 with 64 females and male 67 (male: female ratio of 1). Among 131 participants, 60 were with T2DM and 71 were normal control. Our study showed a significant strength of association between the UACr with the urine MAU (r=0.760, p<0.001), where-as the SAU was associated with MAU excretion in urine (0.52, p<0.001). The UACr was also significantly associated with the HbA1c (r=0.25, p=0.01). Conclusions: Urine microalbuminuria and HbA1c were significantly correlated with the ratio of uric acid to creatinine in the serum. The serum uric acid creatinine ratio (UACr) is a good predictor for predicting renal damage in patients with diabetes mellitus at an early stage of illness.